IMPLEMENTATION OF THE CONCEPT OF LIFELONG LEARNING IN PERSONNEL MANAGEMENT IN THE PUBLIC SERVICE: SOME THEORETICAL ASPECTS - Salnikov, Oleksiy; Kozlova, Liudmyla (Public Administration and Regional Development, 2020)
The article is devoted to the consideration of theoretical principles and practical possibilities for the introduction of the concept of lifelong learning in the management of personnel of public authorities. Attention is also focused on foreign experience and defining the basic principles of this concept, its relevance for the domestic system of public administration. The article defines the basic concepts and terms, systematized scientific views on the interpretation of basic concepts. In the information society, achieving life success is impossible without constant development of new knowledge, without improving skills and competencies that will contribute to the formation of a creative personality that can not only independently and critically rethink existing challenges of daily work, but to form new solutions. Everyone today lacks certain knowledge and needs to update it regularly. The principle of "lifelong learning" applies in all civilized countries. Both professionally successful people and unemployed citizens who have become so due to the impossibility of employment or lack of the necessary qualifications strive for professional retraining and advanced training. Sociological research shows that in modern conditions the number of people continuing their education and learning new professions and qualifications is growing. This is due to many reasons: the professional knowledge acquired by a person quickly becomes obsolete; once popular professions become unclaimed; the person loses interest in the chosen profession; a person seeks to improve the quality of professional knowledge and build a career; a person increases his competitiveness by obtaining an additional specialty or qualification. In recent decades, the system of knowledge generation and transfer has changed dramatically, and their volume has increased many times over. In the case of the unification of humanity on the basis of certain values and goals, of course, one of the priority factors is continuing education. Continuity acts in the modern cultural and educational context as an idea, the principle of learning, the quality of the educational process, the condition of human development. Today it is impossible to prepare a person for professional activity for life at once, even in 5 or 6 years. Scientific research shows that at the present stage about 5% of theoretical and 20% of professional knowledge is annually updated. For example, the unit of measurement of specialist knowledge, which is accepted in the United States, determines the period of "half-life" of competence, ie its reduction by 50% due to new information, shows that in many professions this period occurs in less than 5 years. Thus, for our higher education system, competence often becomes irrelevant before graduation.